The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/yco.0000000000000490
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urbanization on cognitive disorders

Abstract: Purpose of review-Cognitive disorders remain a major global burden with an estimated 47 million people living with dementia worldwide. Rates of cognitive disorders are expected to grow, especially as the global population ages. Global trends also indicate that about half of the global population lives in urban settings. To help guide future research, as well as the development of targeted and tailored interventions to prevent and care for people living with cognitive disorders, we present an up-to-date review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
(67 reference statements)
2
29
0
Order By: Relevance
“…Our study is consistent with review articles that found that people living in urban centers tended to develop dementia less than those in rural areas [7,30]. Although there was an unequal distribution or a lack of resources related to better cognitive function (health clinics, bookstores, and libraries) due to the de cit of educated consumer demand or taxes for such resources in lower education communities [26], this may more easily happen in non-urban areas than in urban areas.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study is consistent with review articles that found that people living in urban centers tended to develop dementia less than those in rural areas [7,30]. Although there was an unequal distribution or a lack of resources related to better cognitive function (health clinics, bookstores, and libraries) due to the de cit of educated consumer demand or taxes for such resources in lower education communities [26], this may more easily happen in non-urban areas than in urban areas.…”
Section: Discussionsupporting
confidence: 90%
“…A systematic review with a meta-analysis concluded that early life rural living was strongly associated with a risk of Alzheimer's disease [30]. In addition, previous studies have mentioned that rural areas had educational inequality, such as more insu cient educational opportunities and less quality of education [7,31]. Although some children left rural areas and proceeded to higher grade schools in urban areas [31], many participants in the current study may live in the same rural areas where they received education for a long time [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that environmental factors such as urbanization and traffic (e.g., highway construction) have been associated with cognitive function in older age [9][10][11][12]. For example, living in cities appears to reduce the risk of cognitive impairment, although the exact reasons are unclear [12,13].…”
Section: Introductionmentioning
confidence: 99%